Evaluation Of Mechanical And Interfacial Properties Of Kenaf Filler/Poly (Lactic Acid) Composites - Idrus, Nurul Athira (Universiti Sains Malaysia, 2022)
The mechanical properties of this biocomposite constituted of kenaf filler and Polylactic acid (PLA) matrix were examined. Mechanical sieving after drying produced two different kenaf filler sizes, KFA (50-100 mesh) and KFB (pass through 100 mesh). Using a single-screw extruder with variable particle loading between 10 wt%, 20 wt%, and 30 wt% for each filler size, a granular bio-composite was produced. Using an injection moulding method, a specimen was produced. The ASTM standard was utilised to evaluate the composites's mechanical properties. KFA has a density of 1.3414 g/cm3 and a filler aspect ratio of 2.2, whereas KFB has a density of 1.3874 g/cm3 and an aspect ratio of 1.9. As the filler loading grew, the tensile strength of the material decreased due to poor interfacial adhesion caused by chemical bonding. The aspect ratio and weight fraction of filler in PLA/KF composites affected their mechanical properties. There was a comparison between experimental data and various theoretical models. The experimental data were compared to composite models including Nicholais and Narkis, Turcasanyi, Nielsens, Kernel, and Halpin-Tsai. The correlation with Turcsanyi and Kernel's model is good, however Nielsens, Nicholais & Narkis’s model conclusions overestimated the experimental data. The ash content and thermal stability of this PLA are marginally enhanced in comparison to the PLA used as a baseline. For high-performance polymer biocomposites, kenaf filler could be an acceptable reinforcement.